Development Of Image-Based Learning Media To Overcome Reading Difficulties - Melysa Indriani; Faridah Faridah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to develop picture media in early reading learning for first-grade students of SDN 375 Pasar VI Natal, and to determine the level of feasibility and effectiveness of its use. This study uses the Research and Development (R&D) method with the ADDIE development model consisting of the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were first-grade students at SDN 375 Pasar VI Natal. Data collection techniques were carried out through intervie ws, observations, expert validation questionnaires, and pretest and posttest tests. The results of the study showed that the developed picture media obtained a material validation percentage of 80%, media validation of 91.25%, and language validation of 98.57% with an overall average of 89.94% which is included in the very valid category. The results of the media implementation showed an increase in students' early reading abilities, indicated by the average pretest score of 70.62 increasing to 94.8 in the posttest. In addition, the results of the N-Gain analysis obtained an average score of 0.85 with a high category. Based on these results, it can be concluded that the developed image media is suitable and effective for use in improving the initial reading skills of first grade students at SDN 375 Pasar VI Natal. Keywords: picture media, beginning reading, ADDIE model, elementary school, reading ability.